2015
DOI: 10.1128/aem.04101-14
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic Evidence for Co-Occurring Top-Down and Bottom-Up Controls on Toxic Cyanobacterial Communities

Abstract: Little is known about the molecular and physiological function of co-occurring microbes within freshwater cyanobacterial harmful algal blooms (cHABs). To address this, community metatranscriptomes collected from the western basin of Lake Erie during August 2012 were examined. Using sequence data, we tested the hypothesis that the activity of the microbial community members is independent of community structure. Predicted metabolic and physiological functional profiles from spatially distinct metatranscriptomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 48 publications
(57 reference statements)
2
53
0
Order By: Relevance
“…For example, production of geosmin and 2-MIB by different cyanobacterial strains have been variously linked with light, temperature and nutrient supply (notably phosphorus and nitrogen; Naes et al, 1989;Blevins et al, 1995;Rashash et al, 1995). and Wu et al (1991, for example, hypothesized that cell nitrogen assimilation plays an important role in geosmin production, and indeed recent evidence has demonstrated that nitrogen is coupled with the production of other secondary metabolites such as microcystins and nodularins (Steffen et al, 2015;Davis et al, 2015). Other studies have identified light as a primary driver, reporting relationships between geosmin or 2-MIB production and photosynthetic pigment synthesis Naes et al, 1985;Saadoun et al, 2001;Zhang et al, 2009).…”
Section: Physico-chemical Properties Producers and Occurrencementioning
confidence: 98%
“…For example, production of geosmin and 2-MIB by different cyanobacterial strains have been variously linked with light, temperature and nutrient supply (notably phosphorus and nitrogen; Naes et al, 1989;Blevins et al, 1995;Rashash et al, 1995). and Wu et al (1991, for example, hypothesized that cell nitrogen assimilation plays an important role in geosmin production, and indeed recent evidence has demonstrated that nitrogen is coupled with the production of other secondary metabolites such as microcystins and nodularins (Steffen et al, 2015;Davis et al, 2015). Other studies have identified light as a primary driver, reporting relationships between geosmin or 2-MIB production and photosynthetic pigment synthesis Naes et al, 1985;Saadoun et al, 2001;Zhang et al, 2009).…”
Section: Physico-chemical Properties Producers and Occurrencementioning
confidence: 98%
“…However, other source of diversification in aquatic ecosystems includes biological factors such as viral lysis (Larsen et al., ) or protistan grazing (Jürgens & Matz, ), known as “top‐down control.” So far, little is known about top‐down controllers, such as viruses, which are also expected to affect the active microbial structure in extreme ecosystems such as high‐altitude wetlands. Bottom‐up and top‐down ecosystem forcings were found to act in concert affecting microbial activities of dominant groups, and thus, influence the active community structure in aquatic environments (Pradeep Ram, Chaibi‐Slouma, Keshri, Colombet, & Sime‐Ngando, ; Steffen et al., ). Moreover, bottom‐up and top‐down processes could generate variable effects within different biotic components of the aquatic food‐web under global warming scenarios, changing the net primary production of the system (e.g., Shurin, Clasen, Greig, Kratina, & Thompson, ).…”
Section: Introductionmentioning
confidence: 99%
“…The sudden collapse in the D. circinale population strongly implicates an external biological effector, such as viral lysis or bacterial predation, neither of which was addressed at length within the scope this study. In this regard, numerous studies have demonstrated biotic mechanisms for the rapid dispersal of cyanobacteria from surface waters that may explain this observation, including phage-induced lysis (Proctor and Fuhrman, 1990;Williamson et al, 2002;Matteson et al, 2011;Steffen et al, 2015), bacteria-induced lysis (Rashidan and Bird, 2001), grazing by protists (Ger et al, 2014), algicidal compounds (Luo et al, 2013; and cyanobacterial programmed cell death (Franklin, 2014).…”
Section: Abioticmentioning
confidence: 99%
“…Numerous studies have highlighted the diversity of heterotrophic groups that occur within microbial communities associated with freshwater bloomforming cyanobacteria species (Eiler and Bertilsson, 2004;Wu et al, 2007;Berg et al, 2008;Cheng et al, 2011;Dziallas and Grossart, 2011;Grossart et al, 2011;Wilhelm et al, 2011;Steffen et al, 2012;Woodhouse et al, 2012;Cai et al, 2013;Xing et al, 2013;Bagatini et al, 2014). Further, such studies have demonstrated that, for cyanobacterial-associated microbial communities, despite the identity of these communities being dependent on the cyanobacterial species present (Bagatini et al, 2014), water chemistry, temperature Xing et al, 2013) and ultimately the freshwater system within which the experiment is based, the function of these communities is largely conserved across local and continental spatial scales (Steffen et al, 2012;Penn et al, 2014;Steffen et al, 2015). Fewer studies have assessed how the nature of the cyanobacterial-associated microbial community changes over temporal scales (Wu et al, 2007;Tang et al, 2010;Xing et al, 2013) with changes in cyanobacterial species dominance and biovolume likely to impact on both the composition and function of these groups.…”
Section: Introductionmentioning
confidence: 99%